Minimum Wages and the Integration of Refugee Immigrants - Per Lundborg; Per Skedinger (Research Institute of Industrial Economics (IFN), 2014)
This paper is the first to estimate the effects of minimum wages on the unemployment of refugee immigrants. The collectively agreed minimum wages raise both the incidence of unemployment and days in unemployment considerably for male refugees in Sweden; different estimation methods and models yield robust elasticities in the 1.8-2.0 range. The effects for young natives are about half as large. There are heterogeneous effects with regard to country of origin and time of residence in Sweden for both male and female refugees. We account for spatial trends - a concern in some of the recent literature - as well as industrial trends. It turns out that only the latter affect our results.
Keywords: J23; J61; J64; 330; Minimum; Wages; and; the; Integration; of; Refugee; Immigrants